The Dynamics of the System of Punitive Measures in the Reform of Indonesian Criminal Law The Transformation of the System of Punitive Measures in Indonesia’s New Criminal Code - Dyah Kusumaningtyas Setiyowati; Pujiyono Pujiyono; Irma Cahyaningtyas; Putu George Matthew Simbolon (Jurnal Pembangunan Hukum Indonesia, 2026)
This research is motivated by the status of measures under Article 103(1) of the 2023 Criminal Code, which treats measures as provisions that may only be imposed alongside principal criminal sanctions, thereby contradicting the principle of equivalence between criminal sanctions and measures. The objective of this study is to propose how the provisions regarding administrative sanctions in Law No. 1 of 2023 on the Criminal Code (KUHP 2023) should be strengthened to align with the doctrine of the double-track system. The methodology employed is a normative legal approach, utilising both historical and conceptual perspectives. The research findings indicate that the 2023 Criminal Code has not yet fully implemented the double track system, as the wording of Article 103(1) places measures in a subordinate position to criminal sanctions, thereby hindering the realisation of rehabilitative justice within the Indonesian criminal justice system. Furthermore, Indonesia has yet to issue government regulations providing further guidance on the implementation of measures as mandated by the 2023 Criminal Code. The conclusion that can be drawn is that the wording of Article 103(1) of the 2023 Criminal Code must be revised by removing the phrase that positions measures merely as a supplement to the principal criminal sanction, and Indonesia needs to immediately enact government regulations to ensure the independent application of measures within the national penal system.